2019
DOI: 10.2169/internalmedicine.2162-18
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Infrequent <i>Arcanobacterium haemolyticum</i> Bacteremia Complicated by Foot Decubitus Ulcer: An Educational Reminder for Primary Care Physicians

Abstract: An 81-year-old Japanese man with no history of diabetes mellitus was admitted to our hospital for a fever with a new ulcerative lesion on the left heel. Blood cultures on admission grew Arcanobacterium haemolyticum in aerobic bottles. He was therefore diagnosed with A. haemolyticum bacteremia and osteomyelitis complicated with foot decubitus ulcer. He was successfully treated with intravenous antibiotic therapy and debridement of the left heel. Our case and literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A.haemolyticum can exist be as a co-pathogen as demonstrated in our cases, as noted and same has been suggested by many studies. [8][9][10] Nonetheless in our case series, all patients had localized infections; all blood cultures showed no growth.…”
Section: Discussionmentioning
confidence: 57%
“…A.haemolyticum can exist be as a co-pathogen as demonstrated in our cases, as noted and same has been suggested by many studies. [8][9][10] Nonetheless in our case series, all patients had localized infections; all blood cultures showed no growth.…”
Section: Discussionmentioning
confidence: 57%
“…The included studies were published between 2010 and 2020, mainly with a prospective cohort design. A diverse geographic distribution of the studies was found, with findings from the USA ( n = 3) 34,35 Japan ( n = 3) 27,28,36 and Brazil ( n = 1), 37 and several studies from European countries such as Spain ( n = 2), 24,38 Poland 39 and the Netherlands 26 . Study samples ranged from one (case reports) to 145 patients.…”
Section: Resultsmentioning
confidence: 99%